Increasing Regional Anesthesia Use in a Serbian Teaching Hospital through an International Collaboration - Baysinger, Curtis L.; Pujic, Borislava; Velickovic, Ivan; Owen, Medge D.; Serafin, Joanna; Shotwell, Matthew S.; Braveman, Ferne (Frontiers in Public Health, 2017)
Many low- and middle-income countries (LMICs) report low rates of regional anesthesia (RA) use for cesarean delivery (CD), despite its association with lower maternal major morbidity and mortality. Also, the prevalence of neuraxial analgesia for labor (NAL) is often low in LMICs. We report on the results of a collaboration in clinical education over a multi-year period between Kybele Inc., an international non-profit organization, and Klinicki Centar Vojvodine (CCV), a teaching hospital in Novi Sad, Serbia, to increase RA use for CD and NAL at CCV. From late 2011 through 2015, teams from Kybele participated in annual to biannual didactic conferences and week-long bedside teaching efforts involving obstetric and anesthesia staff from CCV and surrounding hospitals. Ongoing contact occurred at least weekly between Kybele and the host to discuss progress. De-identified quality improvement data on total deliveries, numbers of elective and non-elective CDs, number of vaginal deliveries, type of anesthesia for CD, and the number of NALs were collected. RA use for CD increased to 25% in year 2015 versus 14% in base year 2011 [odds ratio (OR): 2.05; 95% confidence interval (CI): 1.73,2.42; p < 0.001]. NAL increased to 10.5% of laboring women in 2015 versus 1.2% in 2011 (OR: 9.6; 95% CI: 7.2, 12.8; p < 0.001). Greater increases for RA use during non-elective CD were observed between 2011 and 2015 (1.4 versus 7.5% of total CD; OR: 5.52; 95% CI: 2.63, 8.41; p < 0.001) relative to elective CD (12.5 versus 17.5% of total CD; OR: 1.48; 95% CI: 1.23, 1.77; p < 0.001). Overall, RA for CD increased during the 4 year collaboration but was not as great as reported in other countries with similar health-care demographics utilizing a similar program. Detailed descriptions of program interventions and barriers to change at CCV are presented.